Perbedaan Kepuasan Pasien Rawat Inap Di Puskesmas Terakreditasi Dasar dan Terakreditasi Madya - Heti Hanifati Amiroh; Husnul Khotimah; Sri Astutik Andayani (JURNAL KESEHATAN PRIMER, 2020)
Introduction: Increased public awareness of health, will lead to demands for improved health services. One effort to anticipate this situation is to maintain the quality of service, the increasing demands of the community for the quality of health services, so the service function needs to be improved to provide patient satisfaction. The aim of the study was to compare the perceptions of service with the satisfaction of inpatients in the Puskesmas with the status of Basic Accreditation and Middle Accreditation of Bondowoso District. Method: The research design used quantitative research with cross sectional approach with a total sample of 42 people with accidental sampling techniques. Then analyzed by One Way Anova statistical test. Result: The statistical test results were obtained for perceptions of services between basic accreditation health centers and mid-level accreditation health centers with p value = 0.001 (p <0.05), patient satisfaction between primary accreditation health centers and middle accreditation health centers with p value = 0,000 (p <0.05). Conclusion: It was concluded that there was a significant difference in perceptions of service and patient satisfaction with perceptions of service with patient satisfaction in public health centers mid-term accreditation was better than basic accreditation puskesmas. Pendahuluan: meningkatnya kesadaran masyarakat tentang kesehatan, akan mengakibatkan tuntutan peningkatan pelayanan kesehatan. Salah satu upaya mengantisipasi keadaan tersebut dengan menjaga kualitas pelayanan, semakin meningkatnya tuntutan masyarakat akan kualitas pelayanan kesehatan, maka fungsi pelayanan secara perlu ditingkatkan untuk memberi kepuasan pasien. Tujuan penelitian untuk mengetahui perbedaan persepsi pelayanan dengan kepuasan pasien rawat inap di Puskesmas berstatus Akreditasi Dasar dan Akreditasi Madya Kabupaten Bondowoso. Metode: desain penelitian penelitian kuantitatif dengan pendekatan cross sectional. sampel sebanyak 42 orang dengan teknik sampling aksidental. uji statistik One Way Anova. Hasil: uji statistik diperoleh untuk perbedaan pelayanan antara puskesmas akreditasi dasar dan puskesmas akreditasi madya dengan p value = 0,001 (p<0,05), kepuasan pasien antara puskesmas akreditasi dasar dan puskesmas akreditasi madya dengan p value = 0,000 (p<0,05). Kesimpulan: bahwa ada terdapat perbedaan yang signifikan persepsi pelayanan dan kepuasan pasien dengan persepsi pelayanan dengan kepuasan pasien di puskesmas akreditasi madya lebih baik daripada puskesmas akreditasi dasar.